2022
DOI: 10.3233/bmr-210053
|View full text |Cite
|
Sign up to set email alerts
|

Physiotherapy treatment of lateral epicondylitis: A systematic review

Abstract: BACKGROUND: Lateral epicondylitis is a tendinopathy with a prevalence of between 1–3% of the population aged 35–54 years. It is a pathology with a favorable evolution, but with frequent recurrences (which imply an economic extra cost). OBJECTIVE: The objective of this review was to determine the efficacy of physiotherapy treatment for the treatment of epicondylitis and, if any, to identify the most appropriate techniques. METHODS: A systematic search was carried out in October 2020 in the databases of PubMed, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 52 publications
(45 reference statements)
0
9
0
1
Order By: Relevance
“…When patients were able to perform the eccentric exercises without experiencing any pain or discomfort, the load was increased using free weights or therabands. The starting and final positions of eccentric exercises, the increase in the load, and the degree of mild or disabling pain could not be standardized but were tailored to each patient [ 11 ]. The static stretching exercises for LET were performed slowly with the elbow in extension, forearm in pronation, wrist in flexion, and ulnar deviation according to the patient’s tolerance to achieve the best stretching position result for the ECRB tendon.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…When patients were able to perform the eccentric exercises without experiencing any pain or discomfort, the load was increased using free weights or therabands. The starting and final positions of eccentric exercises, the increase in the load, and the degree of mild or disabling pain could not be standardized but were tailored to each patient [ 11 ]. The static stretching exercises for LET were performed slowly with the elbow in extension, forearm in pronation, wrist in flexion, and ulnar deviation according to the patient’s tolerance to achieve the best stretching position result for the ECRB tendon.…”
Section: Methodsmentioning
confidence: 99%
“…The static stretching exercises for LET were performed slowly with the elbow in extension, forearm in pronation, wrist in flexion, and ulnar deviation according to the patient’s tolerance to achieve the best stretching position result for the ECRB tendon. This position was held for 30–45 s before and after each set of eccentric exercises [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A clinical commentary by Vicenzino B et al found evidence for the use of elbow manipulation and therapeutic exercise for LE on a short-term basis [ 9 ]. Manual therapy and eccentric strength training are the two physiotherapeutic treatment methods that have the greatest beneficial effects in treating LE [ 10 ]. In manual therapy both Cyriax approach (Deep transverse friction massage with Mill’s manipulation) and Mulligan mobilization with movement (MWM) decreased pain and improved functional status in lateral epicondylitis patients [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some experts suggested that corticosteroid injection should not be used to treat most patients with tennis elbow who exhibit a symptom duration of less than 12 months and that this approach might be less beneficial to the long-term outcomes of the patient [11]. In the long term, physiotherapy became the best option, followed by a wait-and-see policy, but the recovery period was still long [12]. While Houck et al reported that autologous blood and platelet-rich plasma are effective treatments in the intermediate term [13].…”
Section: Introductionmentioning
confidence: 99%